2022
DOI: 10.1038/s41598-021-04084-z
|View full text |Cite
|
Sign up to set email alerts
|

Atypical dependence of excited exciton energy levels and electron-hole correlation on emission energy in pyramidal InP-based quantum dots

Abstract: We calculate the spectrum of excited exciton states in application-relevant self-assembled pyramidal quantum dots grown in InAs/InP and InAs/AlGaInAs material systems. These types of dots have been recently shown to combine the emission in the third optical fiber window with low surface density and a reasonable level of in-plane symmetry of emitters, which predestines them for studies on single- and entangled-photon emission and for corresponding applications. The spectrum of optically active excited states is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…However, because this mechanism may not be applicable to InAs/GaAs QDs, the exciton g factor lacks a high degree of dependence. Through further research, Gawelczyk found that the excited state energy of pyramidal InAs/InP QDs is opposite to that of the ground-state emission energy, and this atypical relationship must be considered when using optical transitions involving higher exciton states [232].…”
Section: Fundamental Optical Processes Based On Pyramidal Low-dimensi...mentioning
confidence: 99%
“…However, because this mechanism may not be applicable to InAs/GaAs QDs, the exciton g factor lacks a high degree of dependence. Through further research, Gawelczyk found that the excited state energy of pyramidal InAs/InP QDs is opposite to that of the ground-state emission energy, and this atypical relationship must be considered when using optical transitions involving higher exciton states [232].…”
Section: Fundamental Optical Processes Based On Pyramidal Low-dimensi...mentioning
confidence: 99%